ENGLISH LANGUAGE ASSESSMENT AND FEEDBACK AS PERCEIVED BY THE STUDENTS - Sri Endah Kusmartini (Universitas PGRI Palembang, 2013)
AbstractIn this current research, the researcher tried to investigateEnglish language assessment and feedback towards Englishachievement of the students on the basis of their perceptions. The research was conducted in Electrical Engineering Study Program-Electro Department, Sriwijaya State Polytechnic. It was a cross-sectional survey design with 50 samples taken randomly. An open questionnaire was used to collect the data after a pilot study to the instrument conducted. English scoresof the students were taken from the archive of Electro Department, Sriwijaya State Polytechnic. The data were analyzed by categorizing them into each variable and described statistically based on the goals of the research. Most of the respondents perceived that it was necessary to have English language assessment and feedback for learning because both influenced their English achievement.Keywords: assessment, feedback